Factors affecting the demography of a lek-mating bird: the greater prairie-chicken - Nooker, Jacqueline Kay (Kansas State University, 2007)
Sexual selection via female choice and male-male aggression leads to elaboration of male traits. If male traits correlated with reproductive success are honest signals of male quality, survival costs may be associated with the expression of those traits. Testosterone (hereafter ‘T’) may enhance male breeding success, but T can also reduce immunocompetence and survival. Socially monogamous male birds with higher circulating T experience reproductive advantages, but the role of T in lek mating systems is largely unknown. To address these issues, I individually marked and conducted focal behavioral observations of greater prairie-chickens (Tympanuchus cupido) at five lek sites over a 5-year period. Females were fitted with radio-telemetry to monitor nesting success and survival. I examined the relationship between male traits and mating success using multinomial discrete choice models, a statistical method not previously applied to studies of sexual selection. Male mating success was highly skewed at greater prairie-chicken leks with 18.5% of males obtaining 87.2% of all successful copulations (n = 108 males; 85 copulations). Mating success was influenced most by male behavior, followed by several morphological attributes. The role of T was quantified using blood samples and by experimentally implanting a subset of males with T. T did not consistently affect mating success. Non-territorial males had lower T levels than territorial males. Among territory holders, T was unexpectedly negatively correlated with mating success. However, the odds of receiving a copulation were 4.3 times (0.42 to 45.3) greater for T-implanted males than males with sham implants. Future work should explore the interactions among the immune system, parasite load, and mating success of prairie-chickens. Annual survival of male prairie-chickens was not related to mating success, behavior, age or T level, suggesting there is no cost of increased male mating success. Like males, reproductive success of females was also highly skewed because < 10% of nests successfully hatched young. Comparisons of seasonal and annual survival rates indicate that females experience increased mortality during the breeding season relative to the nonbreeding season. Synthesis of field estimates of demographic parameters indicates prairie-chicken populations will decline without changes in rangeland management to reduce predator numbers or provide more nesting cover.
Keywords: Grouse; Female mate choice; Survival; Testosterone; Reproductive success; Sexual selection; Nest success; Biology, General (0306)